PERAN AMAL USAHA MUHAMMADIYAH DAN ‘AISYIYAH DALAM MENURUNKAN STUNTING DI KENAGARIAN TANJUNG BUNGO - Yuliza Anggraini; Lisa Ernita (LPPM Universitas Abdurrab, 2022)
Stunting toddlers in Indonesia reach a prevalence of 30.8%, this figure is 8.9 times higher than the world. Stunting has an impact on the inhibition of the child's height, the child's intelligence level, the decreased role of the immune system, immune function, and metabolic system disorders. It takes cooperation from various parties to deal with stunting, one of which is building partners with various sectors. Muhammadiyah and Aisyiyah are one of the largest organizational partners in Indonesia and are located throughout Indonesia, both cities and villages that can help the government reduce the incidence of stunting. One of them is Kenagarian Tanjung Bungo which has more than 500 charities and members of Muhammadiyah and Aisyiyah. Family and health development is one of the institutional programs of Muhammadiyah and Aisyiyah, with the awareness movement for stunting from the Muhammadiyah and Aisyiyah organizations it is hoped that it can reduce the incidence of stunting in Kenagarian Tanjung Bungo. The research design is a qualitative research with a phenomenological descriptive approach, namely a study that seeks to describe and interpret a phenomenon or concept from the life experiences of several individuals. The purpose of this study was to determine the role of Muhammadiyah and Aisyiyah charities in reducing stunting in Kenagarian Tanjung Bungo. The results showed that the role of Muhammadiyah and Aisyiyah's charitable efforts in Tanjung Bungo Kenagarian was not maximized because there were no policies or appeals from PDM or PDA to participate in helping the government in reducing stunting by making government programs successful. Conclusions PDM or PDA needs to develop policies or rules in order to support government programs so that the participation of Muhammadiyah and Aisyiyah Charities is maximized, especially in order to reduce the incidence of stunting in Indonesia.